A Hypomorphic Dars1D367Y Model Recapitulates Key Aspects of the Leukodystrophy HBSL - Fröhlich, Dominik; Mendes, Marisa I.; Kueh, Andrew J.; Bongers, Andre; Herold, Marco J.; Salomons, Gajja S.; Housley, Gary D.; Klugmann, Matthias (Frontiers in Cellular Neuroscience, 2021)
Hypomyelination with brain stem and spinal cord involvement and leg spasticity (HBSL) is a leukodystrophy caused by missense mutations of the aspartyl-tRNA synthetase-encoding gene DARS1. The clinical picture includes the regression of acquired motor milestones, spasticity, ataxia, seizures, nystagmus and intellectual disabilities. Morphologically, HBSL is characterized by a distinct pattern of hypomyelination in the central nervous system including the anterior brainstem, the cerebellar peduncles and the supratentorial white matter as well as the dorsal columns and the lateral corticospinal tracts of the spinal cord. Adequate HBSL animal models are lacking. Dars1 knockout mice are embryonic lethal precluding examination of the etiology. To address this, we introduced the HBSL-causing Dars1D367Y point mutation into the mouse genome. Surprisingly, mice carrying this mutation homozygously were phenotypically normal. As hypomorphic mutations are more severe in trans to a deletion, we crossed Dars1D367Y/D367Y mice with Dars1-null carriers. The resulting Dars1D367Y/- offspring displayed a strong developmental delay compared to control Dars1D367Y/+ littermates, starting during embryogenesis. Only a small fraction of Dars1D367Y/- mice were born, and half of these mice died with hydrocephalus during the first three weeks of life. Of the few Dars1D367Y/- mice that were born at term, 25% displayed microphthalmia. Throughout postnatal life, Dars1D367Y/- mice remained smaller and lighter than their Dars1D367Y/+ littermates. Despite this early developmental deficit, once they made it through early adolescence Dars1D367Y/- mice were phenotypically inconspicuous for most of their adult life, until they developed late onset motor deficits as well as vacuolization and demyelination of the spinal cord white matter. Expression levels of the major myelin proteins were reduced in Dars1D367Y/- mice compared to controls. Taken together, Dars1D367Y/- mice model aspects of the clinical picture of the corresponding missense mutation in HBSL. This model will enable studies of late onset deficits, which is precluded in Dars1 knockout mice, and can be leveraged to test potential HBSL therapeutics including DARS1 gene replacement therapy.